The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1017/jfm.2020.615
|View full text |Cite
|
Sign up to set email alerts
|

A hyperbolic two-fluid model for compressible flows with arbitrary material-density ratios

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…EL methods generally remain hyperbolic due to the Lagrangian treatment of the particle phase, though they could be susceptible to similar numerical instabilities if inter-particle contact is not treated explicitly (Theofanous and Chang, 2017). Numerous attempts have been made to restore hyperbolicity starting with Stuhmiller (1977), and seems only very recently to be properly resolved (Fox et al, 2020).…”
Section: Ill-posedness and Hyperbolicitymentioning
confidence: 99%
See 3 more Smart Citations
“…EL methods generally remain hyperbolic due to the Lagrangian treatment of the particle phase, though they could be susceptible to similar numerical instabilities if inter-particle contact is not treated explicitly (Theofanous and Chang, 2017). Numerous attempts have been made to restore hyperbolicity starting with Stuhmiller (1977), and seems only very recently to be properly resolved (Fox et al, 2020).…”
Section: Ill-posedness and Hyperbolicitymentioning
confidence: 99%
“…A rigorous analysis of this model showed that it is hyperbolic for gas-particle flows with ρ p /ρ f 1. The following year, Fox et al (2020) extended the model to arbitrary density ratios by including the added mass of the fluid on the particle in addition to fluid-mediated interactions between particles. An additional equation to include R f in the fluid phase was also proposed.…”
Section: Ill-posedness and Hyperbolicitymentioning
confidence: 99%
See 2 more Smart Citations
“…The drag models considered here are also of interest for EE simulation strategies, where detailed particle configuration data is not available. A recent discussion of the properties of such simulations is found in [22].…”
Section: Introductionmentioning
confidence: 99%